2022
DOI: 10.3390/children9060837
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Anorexia in Youth: Cautiously Bridging the Treatment Gap

Abstract: Atypical anorexia nervosa (AAN) is a restrictive eating disorder (ED) that describes individuals who may be normal weighted or overweight; many have a premorbid history of obesity. Pediatric care providers are trained to identify and provide best practices for youth with pediatric obesity; however, most pediatric care providers are not trained to assess and treat restrictive EDs which typically present in youth aged 10 and 14 years. Although individuals with AAN may appear to be within a ‘healthy weight’, many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Hospitalisation was also common across groups, with ~ 40% of non-underweight adolescents in studies reviewed requiring a medical admission. These results correlate with findings of other recent reviews that compare AN and AAN [11,34].…”
Section: Medical Instability In An and Aan Presentationssupporting
confidence: 92%
See 1 more Smart Citation
“…Hospitalisation was also common across groups, with ~ 40% of non-underweight adolescents in studies reviewed requiring a medical admission. These results correlate with findings of other recent reviews that compare AN and AAN [11,34].…”
Section: Medical Instability In An and Aan Presentationssupporting
confidence: 92%
“…A recent review, by Freizinger and colleagues, exploring assessment and treatment in adolescent AAN, in comparison to AN concluded that malnutrition related to rapid or significant weight loss, in the absence of underweight, poses similar risks to health as typical presentations of AN [34]. Similarly, a recent Delphi study exploring research priorities in AAN, identified medical complications arising from the disorder as a high priority [35].…”
Section: Medical Complications In Aanmentioning
confidence: 99%
“…For example, a useful clinical clue in the diagnosis of atypical AN derives from the frequent presence of previous obesity or overweight. The subsequent initiation of a diet, linked to reinforcements derived both from a better perception of the own body image and from environmental stimuli (e.g., positive reinforcement from the family), can subsequently lead to the onset and maintenance of this disorder [ 14 ]. However, culturally, the idea that ‘anorexic thinking’ in itself constitutes a psychiatric problem still seems to be uncommon.…”
Section: Atypical Anorexia Nervosamentioning
confidence: 99%
“…In addition, the possibility of developing comorbidities appears to be the same as in subjects with “typical” AN: specifically, the most prevalent comorbidities are depressive symptoms, obsessive-compulsive disorder and suicidal ideation/self-harm [ 15 ]. As with the classic forms of AN, family-based treatment is the first-line therapy in atypical forms [ 14 ]. It is also well known that the psychopharmacological approach in cases of AN has mixed results: mainly, however, it appears to have a minimal effect both in terms of improving anorexic symptoms and weight recovery [ 16 ].…”
Section: Atypical Anorexia Nervosamentioning
confidence: 99%
“…Adolescents diagnosed with AAN demonstrate higher rates of suicidality compared to peers without eating disorders [4] but exhibit similar rates of self-harm and suicidality compared to peers with AN [5]. Research suggests that adolescents with AAN may display more severe eating disorder psychopathology [5][6][7][8] and comparable levels of poor selfesteem [5] compared to adolescents with AN. While preliminary case-report data exist on the adoption of nutritional guidelines for these patients [9], further comprehensive data are imperative for a more thorough understanding.…”
Section: Introduction 1classification and Definitionmentioning
confidence: 99%